Performance Prediction of a Full-Size Rapid Dampening Suspension in an Ultra-Class Hauler Application - R. K. Soni; T. G. Joseph; M. Curley (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
"Rapid dampening suspension is a proposed suspension design for ultra-class haulers that is intended to avoid metal-to-metal contact inside a strut and under shock loading, thus improving ride quality and ameliorating fatigue loading issues on a hauler structure. Laboratory testing has shown the ability of the proposed design to reduce the opportunity for bottoming out, that is, metal-to-metal contact between the colliding ends of oleo-pneumatic, two-piece suspension struts during the compression cycle. This paper predicts the performance of a full-size rapid dampening suspension strut by applying scaling rules to test the proposed design based on a set of field data from a Caterpillar 797B ultra-class haul truck operating in the oil sands region of the province of Alberta, Canada. The predicted performance of the suspension strut is compared to that of the original equipment manufacturer model, which was monitored on board the truck during field data collection. ¦ KEYWORDS Haul truck, Original equipment manufacturer (OEM), Rapid dampening, Strut, Suspension RÉSUMÉ La suspension à amortissement rapide est une conception de suspension proposée pour des camions de transport de catégorie ultra-class (des engins dont la charge utile dépasse les 320 tonnes métriques), visant à empêcher un contact métal sur métal à l’intérieur d’une jambe de suspension et dans des conditions de choc au chargement. Elle améliore la qualité du roulement et les problèmes de charge de fatigue sur la structure d’un camion de transport. Les essais en laboratoire ont confirmé que la concep¬tion proposée évitera au cylindre interne de heurter le cylindre externe, autrement dit empêchera le contact métal sur métal des jambes de suspension oléopneumatique en deux parties pendant le cycle de compres¬sion. Cet article prévoit la performance d’une jambe de suspension à amortissement rapide à taille réelle en appliquant les lois d’échelle afin de mettre à l’essai la conception proposée, sur la base d’une série de données de terrain relatives à un camion de transport 797B de catégorie ultra-class de Caterpillar (aujourd’hui remplacé par le nouveau modèle 797F) utilisé dans la région des sables bitumineux de la pro¬vince de l’Alberta, Canada. On compare la performance prévue de la jambe de suspension à celle du modèle du fabricant d’équipement d’origine (FEO), qui a été contrôlée à bord du tombereau pendant la collecte des données de terrain. ¦ MOTS CLÉS amortissement rapide, camion de transport, fabricant d’équipement d’origine (FEO), jambe de suspension, suspensionINTRODUCTION Research basis for the paper This paper is based on the unpublished MSc thesis work of El-Sayed (2003), Santos (2007), and Soni (2009) under the direction of Dr. Tim Joseph within the oil sands–equipment interactions program (OsEIP). OsEIP is part of the Alberta equipment–ground interactions syndicate (AEGIS) surface mining research group, School of Mining and Petroleum Engineering, University of Alberta. The aforementioned work spanned a decade of progressive studies into rapid dampening suspension systems, leading to the scale performance indications highlighted here. Although this paper uses a specific Caterpillar 797B suspension strut for field monitoring and as a basis for scale prediction of a modified rapid dampening suspension strut design, the design scaling principles used here could be applicable to any such design change consideration for an oleo-pneumatic suspension system."